Sunlight‐Driven Hydrogen Production Using an Annular Flow Photoreactor and g‐C3N4‐Based Catalysts. Issue 10 (9th May 2018) - Muñoz‐Batista, Mario J.; Rodríguez‐Padrón, Daily; Puente‐Santiago, Alain R.; Kubacka, Anna; Luque, Rafael; Fernández‐García, Marcos
Abstract: Simple modifications of g‐C3 N4 (CN) have been studied to maximize hydrogen production under sunlight irradiation conditions. The relatively low surface area CN obtained was subjected to an exfoliation process which 1) increases available catalytic area and 2) modulates the semiconductor charge photohandling. MnO x and metallic Pt, which can act as co‐catalysts, were subsequently added on the surface of exfoliated or bulk counterparts, producing an active material suitable for sunlight applications. The resulting catalysts were fully characterized using a multi‐technique approach. The combination of results indicates that optical properties are strongly defined by the delaminated process whereas the minority phases do not cause physico‐chemical variation of the CN structure. Materials without Pt did not show activity under the investigated reaction conditions. In addition, the collaborative effect of the minority phases on the exfoliated CN was confirmed through a strict quantum efficiency calculation. Stability of the most active sample was similarly examined. Abstract : Power up with Pt : Simple modifications to graphitic carbon nitride g‐C3 N4 (involving an exfoliation process and the presence of MnOx and Pt) have been studied for hydrogen photoproduction under sunlight‐type illumination conditions and a multi‐lamp annular photoreactor. Materials without Pt did not show activity under the investigated reaction conditions.